Stable Quantitative Resistance Loci to Blackleg Disease in Canola (Brassica napus L.) Over Continents - Raman, Harsh; Raman, Rosy; Diffey, Simon; Qiu, Yu; McVittie, Brett; Barbulescu, Denise Maria; Salisbury, Phil Anthony; Marcroft, Steve; Delourme, Regine (Frontiers in Plant Science, 2018)
The hemibiotrophic fungus, Leptosphaeria maculans is the most devastating pathogen, causing blackleg disease in canola (Brassica napus L). To study the genomic regions involved in quantitative resistance (QR), 259–276 DH lines from Darmor-bzh/Yudal (DYDH) population were assessed for resistance to blackleg under shade house and field conditions across 3 years. In different experiments, the broad sense heritability varied from 43 to 95%. A total of 27 significant quantitative trait loci (QTL) for QR were detected on 12 chromosomes and explained between 2.14 and 10.13% of the genotypic variance. Of the significant QTL, at least seven were repeatedly detected across different experiments on chromosomes A02, A07, A09, A10, C01, and C09. Resistance alleles were mainly contributed by ‘Darmor-bzh’ but ‘Yudal’ also contributed few of them. Our results suggest that plant maturity and plant height may have a pleiotropic effect on QR in our conditions. We confirmed that Rlm9 which is present in ‘Darmor-bzh’ is not effective to confer resistance in our Australian field conditions. Comparative mapping showed that several R genes coding for nucleotide-binding leucine-rich repeat (LRR) receptors map in close proximity (within 200 Kb) of the significant trait-marker associations on the reference ‘Darmor-bzh’ genome assembly. More importantly, eight significant QTL regions were detected across diverse growing environments: Australia, France, and United Kingdom. These stable QTL identified herein can be utilized for enhancing QR in elite canola germplasm via marker- assisted or genomic selection strategies.